Ineffective zoning in protected areas of Bosnia and Herzegovina – case study NP Kozara - Hrelja, Edin; Drešković, Nusret; Čaušević, Amra (Journal for Geography, 2019)
This paper aims to examine inadequate zoning in protected natural areas in Bosnia and Herzegovina, case study - National park Kozara. Protected natural areas are under increasing anthropogenic impact, therefore their adequate zoning is the key to sustainable development. The performed zoning of the Kozara National Park, as well as most of the protected areas in Bosnia and Herzegovina, is inadequate and it is mainly established in order to exploit natural resources. As a confirmation of the above, it indicates that the zone III of protection level, where traditional economic activities are permitted, the construction of housing and tourist infrastructure, occupy a significant part in protected areas. General and specific geographical methods and techniques of research are used in this paper. The main focus is GIS method because throughout which is established significant database and maps of inadequate protection zones in the parks.